Effects of water level gradients on the physiological ecology of Potamogeton crispus - Cheng-Lu Chen; Yi-Ting Chen; Li-Li Xia; Li-Bing Huang; Yong-Jin Wang; Yun Cao (Journal of Freshwater Ecology)
Water level is crucial to the growth and development of wetland plants, in order to study the physiological and ecological responses of Pomatogeton crispus under different water levels, in the study, P. crispus were placed under 50 cm (control) and 60–135 cm water levels following a 15 cm gap gradient for 60 days in a simulation experiment. The results showed that: (1) As the water level gradient increased, the plant height, leaf number and biomass of P. crispus showed a trend of increasing and then decreasing. (2) The concentrations of chlorophyll a (Chl-a), chlorophyll b (Chl-b), chlorophyll a + b (Chl a + b) and carotenoids (Car) showed a multi-peak increasing trend with increasing water level, with the maximum values occurring in the 135 cm water level group. (3) The antioxidant enzymes of P. crispus showed a fluctuating upward trend with increasing water level, and the higher the water level the greater the difference within the group, and rooting activity of P. crispus was significantly increased under elevated water level conditions. (4) The P. crispus grows best in the water level range of 105 ∼ 120 cm, and the growth indexes such as the number of leaves and biomass all reach higher values in the water level of 105 ∼ 120 cm, If the water level is too high or too low, it has an effect on the growth and development of P. crispus.